Exploring equity in global health collaborations: a qualitative study of donor and recipient power dynamics in Liberia - Brigid E. Cakouros; Johannah Gum; D. Levine; Joseph Lewis; Antoinette H Wright; Bernice Dahn; Kristina Talbert‐Slagle (2024)
Global health collaborations between individuals from high-resource and low-resource settings are complex and often built on hierarchical structures and power differentials that are difficult to change. There have been many calls and frameworks developed to facilitate more equity within these collaborations, yet little is known about the lived experiences of global health donors and recipients working within such collaborations and how those experiences can facilitate more equitable collaboration. Liberia, a postconflict, post-Ebola country, provides an ideal setting to study lived experiences of global health collaborations.